A Randomized Controlled Trial of the Korean Version of the Program for the Education and Enrichment of Relational Skills for Young Adults (PEERS®-YA-K) With Autism Spectrum Disorder: A Pilot Study - Oh, Miae; Laugeson, Elizabeth; Kim, Joo-Hyun; Lee, Kyungah; Kim, Jeeyun; Lee, SeungHa; Lim, Bora; Cha, Seyoung; Bong, Guiyoung; Yoon, Nan-He; Bahn, Geon Ho; Yoo, Hee Jeong (Frontiers in Psychiatry, 2021)
Evidence-based social skills interventions for young adults are limited, despite social difficulties in autism spectrum disorder (ASD) persisting after transition to adulthood. The Program for the Education and Enrichment of Relational Skills for Young Adults (PEERS®-YA) is an evidence-based intervention found to be effective in improving relational skills in young adults with ASD. To translate the original American version of the PEERS®-YA treatment manual into Korean, intensive interviews were performed. Based on results from interviews, several rules of dating etiquette and social activities were modified to be culturally sensitive and linguistically appropriate. Next, young adults diagnosed with ASD (18–35 years of age; IQ > 70) and their social coaches were recruited for the randomized controlled trial (RCT). Participants were randomly assigned either to a treatment group (TG; n = 19) or a delayed treatment group (DTG; n = 18). In the analysis of group differences in the TG and DTG, social skills knowledge was improved. The within group analyses showed positive effects of improving social skills knowledge on reducing depression and anxiety symptoms. After modest cultural adaptations focusing on dating and social activities, the implementation of the PEERS®-YA-K was found feasible for the Korean community. This is one of only a few cross-cultural validation trials establishing evidence-based treatment in young adults with ASD. Clinical Trial Registration: This trial was registered at ClinicalTrials.gov, identifier: NCT03310775.